Improving the teaching of “correlation does not equal causation” in Introductory Psychology - Stevens, Courtney; Witkow, Melissa R.; Isbell, Jason (Frontiers in Psychology, 2025)
“Correlation does not equal causation” is perhaps the most familiar phrase to any student or instructor in an Introductory Psychology class. While short and pithy, we argue that this phrase and its variants can lead to confusion among students, who may incorrectly interpret it to mean that “correlation cannot mean causation.” Unfortunately, this misinterpretation trades one type of reasoning error (incorrectly drawing a causal conclusion from a correlational study) for a separate type of reasoning error (incorrectly concluding there cannot be a causal relationship reflected in a correlational study). Drawing on patterns of student responses on an exam question targeting this issue, we demonstrate that this latter reasoning error is observed in over 30% of Introductory Psychology students. We end by proposing a set of possible sources of this confusion and call on instructors of Introductory Psychology to develop and assess methods to better teach this scientific reasoning skill.